The Nucleolar Protein LYAR Facilitates Ribonucleoprotein Assembly of Influenza A Virus - Yang, Cha (J Virol, 2018)
Influenza A viral ribonucleoprotein (vRNP) is responsible for transcription and replication of the viral genome in infected cells and depends on host factors for its functions. Identification of the host factors interacting with vRNP not only improves understanding of virus-host interactions but also provides insights into novel mechanisms of viral pathogenicity and the development of new antiviral strategies. Here, we have identified 80 host factors that copurified with vRNP using affinity purification followed by mass spectrometry. LYAR, a cell growth-regulating nucleolar protein, has been shown to be important for influenza A virus replication. During influenza A virus infection, LYAR expression is increased and partly translocates from the nucleolus to the nucleoplasm and cytoplasm. Furthermore, LYAR interacts with RNP subunits, resulting in enhancing viral RNP assembly, thereby facilitating viral RNA synthesis. Taken together, our studies identify a novel vRNP binding host partner important for influenza A virus replication and further reveal the mechanism of LYAR regulating influenza A viral RNA synthesis by facilitating viral RNP assembly. IMPORTANCE Influenza A virus (IAV) must utilize the host cell machinery to replicate, but many of the mechanisms of IAV-host interaction remain poorly understood. Improved understanding of interactions between host factors and vRNP not only increases our basic knowledge of the molecular mechanisms of virus replication and pathogenicity but also provides insights into possible novel antiviral targets that are necessary due to the widespread emergence of drug-resistant IAV strains. Here, we have identified LYAR, a cell growth-regulating nucleolar protein, which interacts with viral RNP components and is important for efficient replication of IAVs and whose role in the IAV life cycle has never been reported. In addition, we further reveal the role of LYAR in viral RNA synthesis. Our results extend and improve current knowledge on the mechanisms of IAV transcription and replication.